Rivaroxaban of Benefit in STEMI: ATLAS ACS 2-TIMI 51 - Alexander, Lori (MD Conference Express, 2012)
Treatment with a low dose of rivaroxaban, an oral factor Xa inhibitor, has been shown to reduce recurrent cardiovascular (CV) events and offer a survival benefit without a significant increase in fatal bleeding for patients who have had an ST-segment elevation myocardial infarction. Rivaroxaban reduced recurrent CV events across the spectrum of acute coronary syndrome in the Anti-Xa Therapy to Lower Cardiovascular Events in Addition to Standard Therapy in Subjects with Acute Coronary Syndrome—Thrombolysis in Myocardial Infarction 51 [ATLAS ACS 2-TIMI 51; J Mega et al. N Engl J Med 2012] trial.